Penerapan Arsitektur Tropis Dalam Perancangan Pusat Rehabilitasi Narkoba - Lase, Oscar Putra Kasih; Saraswaty, Rina (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2024)
Population growth and the rapid development of globalization have made the province of North Sumatera, especially the city of Medan, experience a major impact, one of which is technological progress which provides added value in people’s lives, and the bad impact is changes in behavior in the community due to drug abuse among the community which causes high levels of crime is getting higher. In this research design, a descriptive qualitative data is processed to obtain data calculations needed for analysis, concepts and design results. This research aims to help the government reduce the number of people who use drugs and save people who abuse the function of these drugs, using a tropical architecture approach that is suitable for the climate in North Sumatra, Indonesia to maximize the function of the building